Development of a Learning Activity Set Using the CIRC Technique to Improve the Reading and Spelling Skills of Prathomsuksa 1 Students - Prempree, Arthittaya; Sangarwut , Anchalee; Srisawad , Paranee (Dhammathas Academic Journal, 2026)
The purposes of this research were: 1) to develop learning activity packages based on the Cooperative Integrated Reading and Composition (CIRC) instructional method to enhance students’ word reading and spelling skills, with an efficiency criterion of 80/80 and an effectiveness index of 0.50 or higher; 2) to compare students’ learning achievement in word reading and spelling before and after instruction; 3) to compare students’ word reading and spelling skills before and after instruction; and 4) to examine students’ satisfaction with the learning management. This study employed a quasi-experimental research design. The target group consisted of 15 first-grade students from Ban Mae Mok School during the first semester of the 2025 academic year, selected through purposive sampling. The research instruments included: 1) three sets of learning activity packages, 2) ten lesson plans, 3) a 20-item learning achievement test, 4) a 20-item word reading and spelling skills test, and 5) a 10-item student satisfaction questionnaire. Data were analyzed using mean, percentage, and standard deviation. The results of the research found that: 1. The CIRC-based cooperative learning activity packages developed for Grade 1 student demonstrated an overall efficiency of 83.60 / 81.25 and an effectiveness index of 0.68, exceeding the prescribed standard. 2. Student’ post-instruction reading-achievement scores (µ = 17.60, σ = 1.24) were significantly higher than their pre-instruction scores (µ = 7.47, σ = 1.68). 3. Student’ reading-and-spelling skills after instruction (µ = 17.27, σ = 1.16) likewise surpassed their pre-instruction skills (µ = 8.40, σ = 1.24). 4. Learner satisfaction with the CIRC-based activities was rated at a high level (µ = 4.44, σ = 0.63). These results confirm that the cooperative CIRC technique is highly effective in enhancing first-grade student’ reading and spelling proficiency while fostering strong learner satisfaction.